Development of limestone based catalyst for biodiesel production from waste cooking oil - Nurul Hidayah, Muhamad @ Ghazali (2015)
Recent developments in biodiesel production have heightened the need for feasible feedstock as this biofuel has high demands because of its advantages. Besides, catalysts play a significant role in improving production of biodiesel fuel. In addition, the determination catalyst is main important for designing a transesterification system. Industrial production of biodiesel employs homogeneous catalysts such as NaOH or KOH which are cannot be recovered and tolerate to soap formation. Thus, the purpose of this research is to develop and characterize the catalyst derived from limestone based. The effect of various condition i.e. different activation catalysts, temperature, WCO to methanol ratio, catalyst loading, reaction time and recyclability on biodiesel production will be studied. Besides, this research also attempts to utilize waste cooking oil as viable feedstock for biodiesel production. A catalyst produced from cement clinker (limestone based) with particle size of 250μm was prepared via wet impregnation method using aqueous solution of potassium hydroxide (KOH) and calcination. The characterizations of catalysts were done using Hammett indicators, X-Ray Fluorescence, SEM, BET and BJH and the product of biodiesel were determined using GC and HPLC. From this research, it was found that KOH activated limestone based catalyst shows a good potential as an alternate for one-step transesterification of low FFA waste cooking oil. Conventional transesterification of WCO using this activated catalyst was found to give the highest WCO conversion to FAME at 96.8% and FAME yield of 60.4% within 60 min of reaction. The end-product from this research also complies with ASTM Standards D6751. The results suggest that the catalyst employed in this work might be useful as a new low cost catalyst for biodiesel production.